Estudio del perfil cognitivo, atención, memoria y funciones ejecutivas de practicantes de baloncestoy taekwondo con edades comprendidas entre los 11 y 14 años (2023)
The sports psychology, throughout history, has played a fundamental role in the sports context, influencing athletes' performance through variables such as attention, memory, and executive functions. These are essential for good sports performance in both individual and team sports.